Influence of aggregate chemical composition on the demulsification rate of emulsified asphalt - Tan, Wei; Zhu, Songxiang; Kong, Lingyun; Peng, Yi; Xu, Lei; Fu, Yaoguo (Frontiers in Materials, 2022)
Efficient demulsification is vital for the application of emulsified asphalt in road construction. In this paper, the effects of the main chemical components of the aggregates (CaCO3, MgO, Fe2O3, SiO2, Al2O3) on the demulsification process of emulsified asphalt were studied by experiment and simulation using a Gompertz model. The findings indicate that the surface energy, specific surface area, and pH of the chemical components of the aggregates are the most important factors influencing the demulsification speed of the emulsified asphalt. The choice of the aggregate's main chemical components can accelerate demulsification speed, with the acceleration effect of Al2O3 on anionic (SDBS) emulsified asphalt and MgO on cationic (STAC) emulsified asphalt both reaching 60%. The fit between the Gompertz model and the experimental viscosity curve is greater than 0.93, which verifies the utility of using the Gompertz approach for studying emulsified asphalt-aggregate mortar viscosity changes. A demulsification evaluation function φ(t) of emulsified asphalt is proposed based on the parameters of the Gompertz model. When φ(t) is close to 1, the emulsified asphalt-aggregate mortar is fully demulsified, and setting φ(t)= 1 allows the demulsification time of the emulsified asphalt-aggregate mortar to be calculated from the Gompertz model parameters.